Educational Inequality versus Income Inequality: An Empirical Investigation - Bayraktar Sağlam, Bahar (The Economic and Social Review, 2021)
Using panel data from 101 countries between 1970 and 2010, this paper explores the dynamic interaction between educational and income inequalities by employing a panel VAR approach with system GMM estimates. The empirical evidence highlights that a more equal distribution of education has contributed significantly to reduce income inequality for low-, middle-, and high-income OECD countries. However, in the higher middle-income and high-income OECD countries, the significance of educational inequality disappears once the level of development, educational attainment and the degree of trade openness are included in the analysis. Further results reveal that an unfair distribution of income acts as a barrier to achieve a better distribution of education in the low- and middle-income economies. Specifically, in the low- and lower middle-income countries, educational inequality and income inequality accentuate each other and generate a vicious cycle of inequalities under all estimation techniques and control variables.